2016
DOI: 10.1038/nature17178
|View full text |Cite|
|
Sign up to set email alerts
|

Cerebral cavernous malformations arise from endothelial gain of MEKK3–KLF2/4 signalling

Abstract: Cerebral cavernous malformations (CCMs) are common inherited and sporadic vascular malformations that cause stroke and seizures in younger individuals1. CCMs arise from endothelial cell loss of KRIT1, CCM2, or PDCD10, non-homologous proteins that form an adaptor complex2. How disruption of the CCM complex results in disease remains controversial, with numerous signaling pathways (including Rho3,4, SMAD5 and Wnt/β-catenin6) and processes such as endothelial-mesenchymal transition (EndMT)5 proposed to play causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
377
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(402 citation statements)
references
References 35 publications
24
377
1
Order By: Relevance
“…Accordingly, it has been reported that CCM3 mouse mutants only develop lesions in conjunction with severe astrocytosis at the lesion site, suggesting that injury of astrocytes may play a role in lesion formation (Louvi et al, 2011), a notion consistent with clinical reports of CCM developing or expanding after physical trauma, injury, or radiation (Cutsforth-Gregory et al, 2015, Louvi et al, 2011). Furthermore and importantly, the development of CCM lesions induced by endothelial-specific conditional knockout of CCM genes in neonatal mice is highly restricted, both spatially and temporally, despite the pan-endothelial deletion of CCM genes (Boulday et al, 2011, Chan et al, 2011, Gibson et al, 2015, Zhou et al, 2016). This clearly demonstrates that the homozygous loss of CCM genes is not fully sufficient to cause CCM lesion formation and disease progression, and suggests the necessary contribution of additional triggers occurring locally, which may include micro-environmental stress factors or brain injuries.…”
Section: Current Knowledge Of the Molecular Basis And Mechanisms Of Cmentioning
confidence: 99%
“…Accordingly, it has been reported that CCM3 mouse mutants only develop lesions in conjunction with severe astrocytosis at the lesion site, suggesting that injury of astrocytes may play a role in lesion formation (Louvi et al, 2011), a notion consistent with clinical reports of CCM developing or expanding after physical trauma, injury, or radiation (Cutsforth-Gregory et al, 2015, Louvi et al, 2011). Furthermore and importantly, the development of CCM lesions induced by endothelial-specific conditional knockout of CCM genes in neonatal mice is highly restricted, both spatially and temporally, despite the pan-endothelial deletion of CCM genes (Boulday et al, 2011, Chan et al, 2011, Gibson et al, 2015, Zhou et al, 2016). This clearly demonstrates that the homozygous loss of CCM genes is not fully sufficient to cause CCM lesion formation and disease progression, and suggests the necessary contribution of additional triggers occurring locally, which may include micro-environmental stress factors or brain injuries.…”
Section: Current Knowledge Of the Molecular Basis And Mechanisms Of Cmentioning
confidence: 99%
“…5 A′′-F′′ and U). Previous work showed that KLF2/4 are up-regulated following CCM loss in endothelial cells (29)(30)(31)(32)(33). KLF2/4 signals were increased in the cerebellum of cKO mice, but the drugs did not reverse this effect (Fig.…”
Section: Combined Treatment Reverses Outcomes Of Endothelial Ccm3 Losmentioning
confidence: 90%
“…Combined treatment with fluvastatin and zoledronate appears to have effects comparable to sulindac sulfide on survival; both approaches also reduced lesion burden, although slight differences in analyses preclude direct comparisons. Because endothelial gain of MEKK3 was suggested in CCM1 disease (33), future studies will likely test inhibitors of this cascade. In conclusion, fluvastatin/zoledronate combination therapy, which effectively inhibits the mevalonate pathway, warrants further evaluation as a pharmacological intervention in familial and potentially in sporadic CCM disease.…”
Section: Discussionmentioning
confidence: 99%
“…KLF4 activation has been recently identified as the major inducer of EndMT in cerebral cavernous malformations, suggesting that KLF4 might be a key trigger of pathological EndMT [80,81]. Additional regulators of EndMT include Notch signaling, several miRs, endothelin 1, Tie1 tyrosine kinase receptors, and sonic hedgehog signaling, providing a wide range of potential targets to regulate EndMT in pathological conditions [29,37,[82][83][84][85][86][87].…”
Section: Endothelial-to-mesenchymal Transition Activationmentioning
confidence: 98%